RNAi Therapeutics: Principles, Prospects and Challenges - Aagaard, Lars (2007)
RNA interference (RNAi) was discovered less than a decade ago and already there are human clinical trials in progress or planned. A major advantage of RNAi versus other anti-sense based approaches for therapeutic applications is that it utilizes cellular machinery that efficiently allows targeting of complementary transcripts, often resulting in highly potent down-regulation of gene expression. Despite the excitement about this remarkable biological process for sequence specific gene regulation, there are a number of hurdles and concerns that must be overcome prior to making RNAi a real therapeutic modality, which include off-target effects, triggering of type I interferon responses, and effective delivery in vivo. This review discusses mechanistic aspects of RNAi, the potential problem areas and solutions and therapeutic applications. It is anticipated that RNAi will be a major therapeutic modality within the next several years, and clearly warrants intense investigation to fully understand the mechanisms involved.